2020
DOI: 10.3390/polym12112574
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Microchannel and Micromold Surface Polishing for Rapid, Low-Quantity Polydimethylsiloxane and Thermoplastic Microfluidic Device Fabrication

Abstract: Polymer-based micromolding has been proposed as an alternative to SU-8 micromolding for microfluidic chip fabrication. However, surface defects such as milling marks may result in rough microchannels and micromolds, limiting microfluidic device performance. Therefore, we use chemical and mechanical methods for polishing polymer microchannels and micromolds. In addition, we evaluated their performance in terms of removing the machining (milling) marks on polymer microchannel and micromold surfaces. For chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In addition, the lowest value of surface roughness (0.173 µm) was obtained when the following values were chosen: a spindle speed of 20 000 rpm, a feed rate of 300 mm min −1 , and a depth cut of 20 µm. Tsao and Wu [ 131 ] investigated micromachining effects on COC surface roughness. They evaluated the surface roughness after milling at spin speeds ranging from 10 000 to 30 000 rpm and feed rates of 1 to 9 mm s −1 .…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…In addition, the lowest value of surface roughness (0.173 µm) was obtained when the following values were chosen: a spindle speed of 20 000 rpm, a feed rate of 300 mm min −1 , and a depth cut of 20 µm. Tsao and Wu [ 131 ] investigated micromachining effects on COC surface roughness. They evaluated the surface roughness after milling at spin speeds ranging from 10 000 to 30 000 rpm and feed rates of 1 to 9 mm s −1 .…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…We showed that this roughness can be mitigated by surface treatment with chloroform vapour. It was previously reported that the use of chloroform, cyclohexane, and acetone for chemical polishing is an effective method to reduce the surface roughness of various machined thermoplastic materials 25 , 26 , 45 , 46 . After exposure to chloroform vapour, we also observed a clear improvement in the surface quality of the micromilled channel.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, micromolding is a technique for the fabrication of microfluidics in polymers using molds with a negative of the desired geometry. Although micromolding technology requires several steps including the mold preparation, an imprint of polymer material, curing of the polymer, separation, and bonding, it can be utilized in many biomedical applications [ 33 , 34 , 35 ]. In addition, many hybrid fabrication technologies are proposed in the literature to overcome existing drawbacks of the previously mentioned technologies and reduce the price and fabrication time.…”
Section: Introductionmentioning
confidence: 99%